CT findings of high-attenuation pulmonary abnormalities - Ceylan, Naim (Springer-Verlag, 2010)
OBJECTIVES: To review the computed tomography (CT) findings of common and uncommon high-attenuation pulmonary lesions and to present a classification scheme of the various entities that can result in high-attenuation pulmonary abnormalities based on the pattern and distribution of findings on CT. BACKGROUND: High-attenuation pulmonary abnormalities can result from the deposition of calcium or, less commonly, other high-attenuation material such as talc, amiodarone, iron, tin, mercury and barium sulphate. CT is highly sensitive in the detection of areas of abnormally high attenuation in the lung parenchyma, airways, mediastinum and pleura. The cause of the calcifications and other high-attenuation conditions may be determined based on the location and pattern of the abnormalities within the lung parenchyma and knowledge of the associated clinical features. RESULTS: We have presented a diagnostic approach based on the presence and distribution of five main patterns of high-attenuation conditions on CT: (1) small hyperdense nodules, (2) large calcified nodules or masses, (3) high-attenuation linear or reticular pattern, (4) high-attenuation consolidation and (5) high attenuation extraparenchymal lesions. CONCLUSIONS: Some high-attenuation pulmonary abnormalities have characteristic CT findings suggesting the correct diagnosis. In other diseases, a combination of clinical features and radiological findings can significantly improve diagnostic accuracy.